2023
DOI: 10.1002/jor.25626
|View full text |Cite
|
Sign up to set email alerts
|

Proprioception‐related gene mutations in relation to the aetiopathogenesis of idiopathic scoliosis: A scoping review

Abstract: Since idiopathic scoliosis is a multifactorial disorder, the proprioceptive defect is considered one of its etiological factors. Genetic studies have separately revealed this relationship, yet it remains indeterminate which specific genes that related to proprioception contributed to the initiation, progression, pathology, and treatment outcomes of the curvature. A systematic search was conducted on four online databases, including PubMed, Web of Science, Embase, and Academic search complete. Studies were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…Recent research has focused on idiopathic scoliosis-related genes. Several types of pathogenic gene mutations have been identified in idiopathic scoliosis through genetic studies; however, no single gene responsible for idiopathic scoliosis has been found so far [69][70][71][72][73].…”
Section: Genetics and Epigeneticsmentioning
confidence: 99%
“…Recent research has focused on idiopathic scoliosis-related genes. Several types of pathogenic gene mutations have been identified in idiopathic scoliosis through genetic studies; however, no single gene responsible for idiopathic scoliosis has been found so far [69][70][71][72][73].…”
Section: Genetics and Epigeneticsmentioning
confidence: 99%